2023
DOI: 10.3390/biology12020248
|View full text |Cite
|
Sign up to set email alerts
|

Submerged and Solid-State Fermentation of Spirulina with Lactic Acid Bacteria Strains: Antimicrobial Properties and the Formation of Bioactive Compounds of Protein Origin

Abstract: The aim of this study was to investigate the changes in bioactive compounds (L-glutamic acid (L-Glu), gamma-aminobutyric acid (GABA) and biogenic amines (BAs)) during the submerged (SMF) and solid-state (SSF) fermentation of Spirulina with lactobacilli strains (Lacticaseibacillus paracasei No. 244; Levilactobacillus brevis No. 173; Leuconostoc mesenteroides No. 225; Liquorilactobacillus uvarum No. 245). The antimicrobial properties of the untreated and fermented Spirulina against a variety of pathogenic and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…Analyses of the concentrations of L-glutamic acid (L-Glu) and GABA in the Spirulina were carried out using a TSQ Quantiva MS/MS coupled to a Thermo Scientific Ultimate 3000 HPLC instrument (Thermo Scientific, Waltham, MA, USA). All methods are described by Tolpeznikaite et al in detail [ 28 ]. An analysis of the fatty acid (FA) profile of the Spirulina samples was performed using a gas chromatograph GC 2010 Plus (Shimadzu Europa GmbH, Duisburg, Germany) equipped with a mass spectrometer, GC-MS QP2010 (Shimadzu Europa GmbH, Duisburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the concentrations of L-glutamic acid (L-Glu) and GABA in the Spirulina were carried out using a TSQ Quantiva MS/MS coupled to a Thermo Scientific Ultimate 3000 HPLC instrument (Thermo Scientific, Waltham, MA, USA). All methods are described by Tolpeznikaite et al in detail [ 28 ]. An analysis of the fatty acid (FA) profile of the Spirulina samples was performed using a gas chromatograph GC 2010 Plus (Shimadzu Europa GmbH, Duisburg, Germany) equipped with a mass spectrometer, GC-MS QP2010 (Shimadzu Europa GmbH, Duisburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…However, GABA levels in fermented foods depend on the conditions of the fermentation process [ 27 ]. Our previous studies showed that fermentation with selected LAB strains is suitable technology for increasing the concentration of GABA in Spirulina [ 28 ]. Additionally, our previous studies showed that fermenting bovine colostrum improves it safety characteristics and functional properties, including its antimicrobial properties [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method is particularly effective for microorganisms that thrive in high-moisture environments, such as bacteria. It has the benefit of facilitating the purification of bioactive peptides produced during the process (Tolpeznikaite et al, 2023). On the other hand, solid-state fermentation consists of microbial growth on nutrientrich solid substrates.…”
Section: Microbial Fermentationmentioning
confidence: 99%
“…Likewise, other research data showed that the phycocyanin, polyphenols and γ‐linolenic acid in Arthrospira have an inhibitory effect on Escherichia coli , Bacillus subtilis and Aspergillus flavus (Metekia et al ., 2021). Arthrospira platensis with Lacticaseibacillus paracasei , Levilactobacillus brevis , Leuconostoc mesenteroides and Liquorilactobacillus uvarum in submerged and solid‐state fermentation have an inhibitory effect on Staphylococcus aureus (Tolpeznikaite et al ., 2023). In addition, the anti‐bacterial activity of A. platensis extracts varied depending on their composition.…”
Section: Functional Properties Of Arthrospira Platensismentioning
confidence: 99%